Model for integrated project management - Schieg, Martin (Journal of Business Economics and Management, 2009)
Although there has been important research on construction management’s life cycle, stakeholders, micro and macroenvironment, there has not been a model defined that can link the above. This while the need to integrate construction management’s life cycle, stakeholders, micro and macroenvironment into both theory and practice is essential. The Model for integrated project management, described in this paper, consists of six stages. The purpose of this study is also to examine micro and macroenvironment impact on efficiency of project managers and project performance, based on the proposed Model. We conclude that the proposed Model offers a promising research toward improving construction management efficiency through giving construction managers method for enhancing a project’s efficient micro and macroenvironment. First Publish Online: 09 Jun 2011